Medium Time Heating of Syrop from Red Betel Leaf (Piper crocatum ruiz pav) Can Reduce Carcinoembryonic Antigen (CEA) Level Among Adult Women in Southeast Sulawesi, Indonesia - Hariani, Hariani; Wiralis, Wiralis; Teguh Faturrahman, Teguh Faturrahman; Suwarni, Suwarni (YCAB Publisher, 2025)
Background: Carcinoembryonic Antigen (CEA) is an immunoglobulin that is strongly suspected to inhibit apoptosis and is closely associated with various cancers and metastases. Red betel leaves have been shown to induce apoptosis in breast cancer cells (MCF-7), activate pro-apoptotic proteins (Bax), and inhibit anti-apoptotic proteins (Bcl-2). Objective: This study aimed to measure the effect of red betel leaf syrup on Carcinoembryonic Antigen (CEA) levels in adult women. Methods: The study employed a pseudo-experimental design with a one-group pre-post-test approach. It was conducted over 6 months (June to December 2019). The study involved 25 participants, selected purposively from the population of adult women aged 40-80 years in Manggadua Village, West Kendari District. The intervention consisted of administering red betel leaf syrup. The intervention was performed 16 times during the study period (once a month). The acceptability of the syrup was assessed using organoleptic tests, and data were analyzed using the ANOVA test and the Wilcoxon signed-rank test to assess changes in CEA levels (μg/dL) after the intervention. Results: Formula F2 was selected as the intervention material. CEA levels showed an average of 2.8760 ± 1.99 ng/ml before the intervention (pre-test) and 3.4920 ± 2.58 ng/ml after the intervention (post-test). Statistical analysis revealed a significant difference in CEA levels (p ≤ 0.05, sig. 0.00). Of the 25 samples, 6 showed a negative difference, 18 showed a positive difference, and 1 remained unchanged, with a z-value of -3.217, indicating that pre-test CEA levels were higher than post-test levels. These results suggest that there was an average decrease in CEA levels following the intervention. Conclusion: The pre-test CEA levels were higher than the post-test levels, with a z-value of -3.217, indicating a decrease in CEA levels after the administration of red betel leaf syrup with medium heat and 16 doses. Keywords:CEA levels; formulation; red betel leaf syrup; honey